2020
DOI: 10.1002/aisy.202000148
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Crystal Polymer‐Based Soft Robots

Abstract: Soft robots outperform the conventional robots on enhanced safety for human-machine interaction, environmental adaptability, and continuous deformation. In this blooming area of fundamental and technological importance, liquid crystal polymer networks and liquid crystal elastomers (referred to as LCNs) have emerged as one of the most valuable candidates for soft robots due to their complex, large, and reversible shape change capabilities. To date, much research effort, mainly regarding chemical synthesis, fabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 137 publications
(211 reference statements)
0
54
0
Order By: Relevance
“…[10][11][12] Moreover, the anisotropic mechanical properties of the LCEs can be harnessed to program their shape changes, enabling complex deformations including bending, coiling, twisting, and helixing. [3,13,14] Recently, significant progress has been achieved in the field of LCEs for materials synthesis, [15][16][17][18][19] fabrication, [16,[20][21][22][23][24] and expansion of LCE applications., [25][26][27][28][29][30][31] which has led to the renaissance of LCEs from both scientific and engineering aspects. However, the preparation of LCEs as actuators typically requires mesogen alignment prior to cross-linking, which leads to complicated fabrication processes unlike those required for fabricating conventional elastomers.…”
mentioning
confidence: 99%
“…[10][11][12] Moreover, the anisotropic mechanical properties of the LCEs can be harnessed to program their shape changes, enabling complex deformations including bending, coiling, twisting, and helixing. [3,13,14] Recently, significant progress has been achieved in the field of LCEs for materials synthesis, [15][16][17][18][19] fabrication, [16,[20][21][22][23][24] and expansion of LCE applications., [25][26][27][28][29][30][31] which has led to the renaissance of LCEs from both scientific and engineering aspects. However, the preparation of LCEs as actuators typically requires mesogen alignment prior to cross-linking, which leads to complicated fabrication processes unlike those required for fabricating conventional elastomers.…”
mentioning
confidence: 99%
“…This indirect heating strategy allows for the localized and efficient temperature control of the polymer system, where the actuation can be precisely controlled in larger LCE systems. [ 94 ]…”
Section: Mechanisms For Electrically Driven Actuationmentioning
confidence: 99%
“…As a type of ordered crosslinked polymer, liquid crystal elastomers (LCEs) have shown remarkable structural transformations by patterning the complex molecular orientations [ 7 ]. The change in the molecular ordering of LCE under external stimuli such as light [ 8 ], heat [ 9 ], or humidity [ 10 ] gives rise to a variety of three-dimensional (3D) shape morphs thanks to its anisotropic elasticity [ 11 , 12 , 13 ]. For example, Ware et al demonstrated arrays of cones and anti-cones transformed from a flat LCE film by pixelating its two-dimensional (2D) director field [ 14 ].…”
Section: Introductionmentioning
confidence: 99%